Coagulation Disorder following Red Clover (Trifolium Pratense) Misuse: a Case Report - Karimpour-Reihan, Sahar (Adv J Emerg Med, 2018)
INTRODUCTION: An increasing variety of alternative health care products and supplements known as over-the-counter (OTC) or non-prescription herbal medicines are taken by patients for different reasons. Unfortunately, these self-prescribed remedies have many food and drug interactions and unknown adverse effects and can lead to some important consequences. CASE PRESENTATION: Here a case of bleeding disorder in a 28-year-old woman taking red clover is reported. She had no history of warfarin use, but warfarin was detected in her blood serum analysis. CONCLUSION: This agent is a source of natural coumarin and can cause an increase of international normalized ratio (INR) and bleeding. It is important that prescribers be alert to the possible disadvantage of herbal remedies and also probable herb-drug and herb-food interactions.